“I don’t belong here”: experiences of substance use and treatment compliance among young adults in Lango, Uganda - Enon, Prossy Lynda; Nalunkuuma, Joan; Ouma, Samuel (Frontiers in Public Health, 2025)
IntroductionSubstance Use Disorders (SUDs) are a leading cause of disability and premature mortality among youth globally. A significant number of young people in sub-Saharan Africa (SSA) are reported to have SUDs and very few seeking help. The actual reasons for poor health-seeking behaviors and non-compliance remain largely unknown. The aim of this study was to examine the experiences of substance use, health seeking behaviors and treatment compliance among young adults diagnosed with SUDs in the Lango sub region of Uganda.MethodsThis cross-sectional-qualitative study employed a phenomenological research design. Individual face-to-face audio-recorded Semi-structured interviews were conducted and thematically analyzed.ResultsThe study involved 10 participants aged between 18 and 35 years, four of whom were female. Key findings include participants’ early exposure to alcohol at home and through peer influence; involuntary health seeking behavior enforced by family and largely negative attitudes to SUD treatment under three major themes: 1) exposure to and maintenance of the use of substances; 2) circumstances of seeking treatment for SUDs; and 3) general ambivalence and negative attitudes toward treatment for SUDs.DiscussionLimited understanding of SUDs as serious health problems amidst increasing accessibility to more psychoactive substances in the community continues to impede health-seeking behavior and compliance with treatment. Concerted efforts aimed at increasing public mental health awareness of SUDs and innovative culturally sensitive clinical interventions can help reduce the morbidity and mortality associated with substance use.